St. Louis enhancing engagement and retention (STEER) in HIV/AIDS care: a participatory intersectional needs assessment for intervention and implementation planning - Humphries, Debbie L.; Marotta, Phillip; Hu, Yue; Wang, Victor; Gross, Greg; Rucker, Darius; Jones, Johnnie; Alam, Faiad; Brown, Tawnya; Spiegelman, Donna; Carter, Chelsey R. (Frontiers in Public Health, 2025)
BackgroundMissouri is one of seven priority states identified by the Ending the HIV Epidemic Initiative, and St. Louis contains almost half of the people living with HIV (PLWH) in Missouri. As St. Louis has a marked history of structural racism and economic inequities, we utilized the Intersectionality Based Policy Analysis (IBPA) framework to guide a participatory needs assessment for planning and program development.MethodsThe planning team included researchers, the lead implementer from our community partner, and two community representatives, and had biweekly 60–90 min meetings for 18 months. The planning team approved all research materials, reviewed and interpreted results, and made decisions about recruitment, conduct of the needs assessment, and development of the planned intervention. The needs assessment integrated information from existing data, (1) interviews with (a) PLWH (n = 12), (b) community leaders (n = 5), (c) clinical leaders (n = 4), and (d) community health workers (CHWs) (n = 3) and (e) CHW supervisors (n = 3) who participated in a Boston University-led project on CHWs in the context of HIV and (2) focus groups (2 FG, 12 participants) with front-line health workers such as peer specialists, health coaches and outreach workers. A rapid qualitative analysis approach was used for all interviews and focus groups.ResultsThe IBPA was used to guide team discussions of team values, definition and framing of the problem, questions and topics in the key informant interviews, development of the logic model of the problem, and all results. Applying the IBPA framework contributed to a focus on intersectional drivers of inequities in HIV. The effective management of HIV faces significant challenges from high provider turnover, insufficient integration of CHWs into care teams, and organizational limitations in tailoring treatment plans. Increasing use of CHWs for HIV treatment and prevention also faces challenges. People living with HIV (PLWH) encounter multiple barriers including stigma, lack of social support, co-morbidities, and difficulties in meeting basic needs.ConclusionAddressing intersectional drivers of health inequities may require multi-level, structural approaches. We see the IBPA as a valuable tool for participatory planning that emphasizes equity and integrates community engagement principles in program and implementation design for improving HIV outcomes.